Solid electrolyte material, nonaqueous electrolyte secondary battery, and method for producing solid electrolyte material

By using polymer materials with alkali metal ion acidic functional groups and crosslinked structures in the nonaqueous electrolyte secondary battery, the problem of difficulty in achieving ion conductivity and non-aqueous solvent separation in the prior art is solved, and more efficient battery performance and reliability are achieved.

CN119895615APending Publication Date: 2025-04-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380066676.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-27
Filing Date
2023-08-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve ion conductivity and separation of nonaqueous solvents in a nonaqueous electrolyte secondary battery.

Method used

A polymer material with acidic functional groups with alkali metal ions bonded to the main chain, which has a crosslinked structure and electron donating polar groups, and these characteristics achieve ion conductivity and separation of non-aqueous solvents.

Benefits of technology

It realizes the separation of ion conductivity and non-aqueous solvents in a nonaqueous electrolyte secondary battery, and improves the performance and reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895615A_ABST
    Figure CN119895615A_ABST
Patent Text Reader

Abstract

This solid electrolyte material contains a polymer in which an acidic functional group having an alkali metal ion is bonded to a main chain, and the polymer has a crosslinked structure containing an electron-donating polar group. A non-aqueous electrolyte secondary battery according to the present disclosure is provided with a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator, and a non-aqueous electrolyte, and satisfies at least one selected from the group consisting of (A) to (D): (A) the non-aqueous electrolyte secondary battery is further provided with a film containing the solid electrolyte material according to the present disclosure; and a film provided on a surface of at least one type of electrode selected from the group consisting of the positive electrode and the negative electrode, said surface facing the separator. (B) The nonaqueous electrolyte secondary battery is further provided with a film comprising the solid electrolyte material of the present disclosure, the film being provided on the surface of particles of at least one type of active material selected from the group consisting of a positive electrode active material and a negative electrode active material. (C) The nonaqueous electrolyte secondary battery is further provided with a film comprising the solid electrolyte material of the present disclosure, the film being provided on at least a part of the surface of the separator. (D) The separator contains the solid electrolyte material of the present disclosure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte material, a nonaqueous electrolyte secondary battery, and a method for producing the solid electrolyte material. Background Art

[0002] Non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are widely used in applications requiring high capacity such as automotive applications and power storage applications. Non-aqueous electrolyte secondary batteries generally include an electrode body in which a positive electrode and a negative electrode are stacked or wound with a separator interposed therebetween, and a non-aqueous electrolyte.

[0003] As one of the means for improving battery performance, for example, separation technology for improving the components of the battery can be cited. In recent years, solid electrolyte materials used in batteries are being actively studied. Such solid electrolyte materials can not only be used as a substitute for electrolytes, but also as materials for covering electrode active materials. For example, Patent Document 1 discloses an all-solid-state lithium battery, which comprises: a lithium ion conductive solid electrolyte with sulfide as the main body and an active material whose surface is covered with a lithium ion conductive oxide.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2007 / 004590 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The solid electrolyte material used for separation between components of a non-aqueous electrolyte secondary battery needs to have separation properties with respect to the non-aqueous solvent used in the battery and ion conductivity of ions involved in the battery reaction.

[0009] The present disclosure provides a solid electrolyte material for a non-aqueous electrolyte secondary battery capable of achieving both ion conductivity and separation properties of a non-aqueous solvent.

[0010] Solutions for solving problems

[0011] The present invention provides a solid electrolyte material, which is a solid electrolyte material for a non-aqueous electrolyte secondary battery.

[0012] The solid electrolyte material comprises a polymer having an acidic functional group having an alkali metal ion bonded to the main chain.

[0013] The polymer has a cross-linked structure including an electron-donating polar group.

[0014] Effects of the Invention

[0015] According to the present disclosure, a solid electrolyte material for a non-aqueous electrolyte secondary battery can be provided that can achieve both ion conductivity and separation properties of a non-aqueous solvent. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a cross-sectional view schematically showing a part of the configuration of the nonaqueous electrolyte secondary battery according to the second embodiment.

[0017] Figure 2 Show Figure 1 The non-aqueous electrolyte secondary battery shown is a cross-sectional view of an electrode when the structure (A) is satisfied.

[0018] Figure 3 Show Figure 1 The cross-sectional view of the active material of the nonaqueous electrolyte secondary battery shown in FIG.

[0019] Figure 4 Show Figure 1 The illustrated nonaqueous electrolyte secondary battery is a cross-sectional view of a separator when the battery satisfies the configuration (C).

[0020] Figure 5 It is a cross-sectional view schematically showing an axial cross section of a nonaqueous electrolyte secondary battery including a wound electrode body, which is an example of the nonaqueous electrolyte secondary battery according to the second embodiment. DETAILED DESCRIPTION

[0021] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0022] (First embodiment)

[0023] The solid electrolyte material according to the first embodiment of the present disclosure is a solid electrolyte material used in a nonaqueous electrolyte secondary battery.

[0024] The solid electrolyte material of the first embodiment includes a polymer in which an acidic functional group having an alkali metal ion is bonded to the main chain, and the polymer has a cross-linked structure including an electron-donating polar group.

[0025] By having the above-mentioned structure, the solid electrolyte material of the first embodiment can have both ion conductivity (for example, lithium ion conductivity) and the ability to separate the nonaqueous solvent used for the nonaqueous electrolyte secondary battery.

[0026] In the polymer contained in the solid electrolyte material of the first embodiment, an acidic functional group having an alkali metal ion is bonded to the main chain. That is, in the polymer contained in the solid electrolyte material of the first embodiment, an anion that becomes an anchor point for an alkali metal ion (for example, a lithium ion) is fixed to the main chain. The acidic functional group functions as an anion that becomes an anchor point for an alkali metal ion, capturing the alkali metal ion. Furthermore, the polymer contained in the solid electrolyte material of the first embodiment has a cross-linked structure. The cross-linked structure contains an electron-donating polar group, and thus becomes a conduction path for the alkali metal ions captured by the acidic functional group and can conduct the alkali metal ions. According to such a mechanism, the solid electrolyte material of the first embodiment can have ion conductivity. In addition, since the polymer contained in the solid electrolyte material of the first embodiment has a cross-linked structure, the solid electrolyte material of the first embodiment can suppress the movement of the non-aqueous solvent. Therefore, the solid electrolyte material of the first embodiment can simultaneously achieve ion conductivity and the separation of the non-aqueous solvent.

[0027] Hereinafter, the polymer contained in the solid electrolyte material of the first embodiment is referred to as the polymer of the first embodiment. In this specification, unless otherwise specified, the polymer means a molecule having a weight average molecular weight (Mw) of 500 or more.

[0028] The main chain of the polymer of the first embodiment can be made of materials that are electrochemically stable and easily suitable for each component of the battery as long as its molecular structure can be achieved. As an example of the main chain, polysaccharides such as polyethylene glycol, polyethylene oxide, polyvinyl alcohol, cellulose, and their derivatives can be listed. For example, the main chain of the polymer of the first embodiment can include at least one selected from the group consisting of cellulose, cellulose derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polyethylene oxide, polyethylene oxide derivatives, polyethylene glycol, and polyethylene glycol derivatives. Among them, the main chain of the polymer of the first embodiment is expected to include at least one selected from the group consisting of cellulose and its derivatives (for example, carboxymethyl cellulose (CMC), etc.). At least a part of the main chain of the polymer of the first embodiment can be composed of cellulose or its derivatives, or it can be substantially composed of cellulose or its derivatives.

[0029] In the polymer of the first embodiment, the acidic functional group is Li + The anionic group of the alkali metal ion pairing and the main chain bonding. That is, the anionic group is fixed to the main chain and does not move, so the conduction of the alkali metal ion with a high migration number can be achieved. The acidic functional group can be bonded to the main chain and can capture the alkali metal ion. As an example of the acidic functional group, carboxylic acid group, sulfonic acid group, phosphite group etc. can be listed. Wherein, from the viewpoint of flame retardancy, phosphite group is ideal.

[0030] A suitable example of the polymer of the first embodiment is for capturing Li + A polymer having a structural unit represented by the following formula (3) in which a phosphorous acid group of an alkali metal ion is bonded to the main chain of cellulose.

[0031]

[0032] In formula (3), Y + represents an alkali metal ion, and m represents a positive integer. The OH group represented by formula (3) may be substituted with a bond of a structural unit constituting a crosslinked structure (ie, a structure formed by reacting with a second compound described later as a crosslinking agent).

[0033] In the structural unit represented by formula (3), it is desirable that 20% to 80%, or 30% to 50% of the OH groups of cellulose are substituted with phosphite groups. With this configuration, the ion conductivity of the solid electrolyte material of the first embodiment can be improved.

[0034] The polymer of the first embodiment may also include structural units such as those shown in formula (3) in which phosphite groups having alkali metal ions are introduced into the main chain of cellulose. The polymer of the first embodiment may be substantially composed of structural units shown in formula (3) in addition to the structural units constituting the cross-linked structure. Here, "the polymer of the first embodiment is substantially composed of structural units shown in formula (3) in addition to the structural units constituting the cross-linked structure" means that in the polymer of the first embodiment, the structural units shown in formula (3) account for 90 mol% or more, preferably 95 mol% or more, relative to the total of all structural units except the structural units constituting the cross-linked structure. The polymer of the first embodiment may be composed only of structural units such as those having phosphite groups having alkali metal ions introduced into the main chain of cellulose in addition to the structural units constituting the cross-linked structure.

[0035] In the polymer of the first embodiment, as the electron-donating polar group contained in the cross-linked structure, for example, ether groups and nitrile groups can be listed. That is, the cross-linked structure can include at least one selected from the group consisting of ether groups and nitrile groups as the above-mentioned polar group. Among them, since the ion conductivity can be further improved, the ether group is ideal. The ether group can be a polyether group. For example, the cross-linked structure in the polymer of the first embodiment can include an ether group as the above-mentioned polar group, and can also include a polyether group. It should be noted that such a cross-linked structure can be formed, for example, by using a polyether-based cross-linking agent containing a polyether group. The ether group is, for example, a polyethylene oxide group.

[0036] The cross-linked structure in the polymer of the first embodiment may include a structure represented by the following formula (1).

[0037]

[0038] The structure of the above formula (1) can be formed by reaction of a hydroxyl group (OH group) and an epoxy group in a cross-linking reaction.

[0039] The cross-linked structure in the polymer of the first embodiment may include a structure represented by the following formula (2).

[0040]

[0041] It should be noted that, in formula (2), n represents a positive integer.

[0042] The structure of the above formula (2) can be formed by reacting a hydroxyl group (OH group) with, for example, polyethylene glycol diglycidyl ether used as a crosslinking agent in a crosslinking reaction.

[0043] The polymer of the first embodiment may include the structural unit represented by the above formula (3) and the structure represented by the above formula (2) as a cross-linked structure. In this case, the polymer of the first embodiment may include the structure represented by the following formula (4).

[0044]

[0045] It should be noted that in formula (4), m and n represent positive integers.

[0046] In the polymer of the first embodiment, the ratio (molar ratio) of the structural units constituting the cross-linked structure to the total of other structural units other than the structural units constituting the cross-linked structure can be appropriately adjusted, for example, taking into account the balance between the target ion conductivity and the separability of the non-aqueous solvent, the type of functional group used in the cross-linking reaction, the polar group contained in the cross-linked structure, etc.

[0047] The solid electrolyte material of the first embodiment may contain other components in addition to the polymer of the first embodiment. For example, a part of the materials used when synthesizing the polymer of the first embodiment, such as a cross-linking agent, may be contained.

[0048] Next, a method for producing the solid electrolyte material according to the first embodiment will be described.

[0049] The method for manufacturing a solid electrolyte material of the first embodiment includes a cross-linking operation of reacting a first compound with a second compound having an electron-donating polar group, wherein the first compound is a polymer having an acidic functional group of an alkali metal ion bonded to a main chain. The first compound includes a first functional group. The second compound includes at least one second functional group in a molecular structural unit, and the second functional group has a function of reacting with the first functional group to form a chemical bond.

[0050] The main chain of the first compound can be a material that is electrochemically stable and easily suitable for each component of the battery as long as its molecular structure can be achieved. As an example of the main chain, polysaccharides such as polyethylene glycol, polyethylene oxide, polyvinyl alcohol, cellulose, and their derivatives can be listed. For example, the main chain of the first compound may include at least one selected from the group consisting of cellulose, cellulose derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polyethylene oxide, polyethylene oxide derivatives, polyethylene glycol, and polyethylene glycol derivatives. Among them, the main chain of the first compound is expected to include at least one selected from the group consisting of cellulose and its derivatives (for example, CMC, etc.). At least a part of the main chain of the first compound may be composed of cellulose or its derivatives, or it may be substantially entirely composed of cellulose or its derivatives.

[0051] The acidic functional group of the first compound is Li + The anionic group of the alkali metal ion pairing and the main chain bonding. That is, the anionic group is fixed to the main chain and does not move, so the conduction of the alkali metal ion with a high migration number can be achieved. The acidic functional group can be bonded to the main chain and can capture the alkali metal ion. As an example of the acidic functional group, carboxylic acid group, sulfonic acid group, phosphite group etc. can be listed. Wherein, from the viewpoint of flame retardancy, phosphite group is ideal.

[0052] The first compound only needs to be a polymer containing an acidic functional group for capturing alkali metal ions and has a weight average molecular weight (Mw) of 500 or more. The molecular weight of the first compound is not particularly limited, for example, Mw is 100,000 or more, and Mw can be 300,000 or more. The alkali metal ions captured by the acidic functional group can be sodium ions (Na + ) or potassium ion (K + ) etc., and it is expected to be lithium ion (Li + ).

[0053] The first compound can be synthesized, for example, by introducing an acidic functional group into the main chain and exchanging the counter cation of the acidic functional group for an alkali metal ion. The following formula (5) shows that in a polymer containing a structural unit represented by formula (3), an alkali metal ion (Y + ) is lithium ion (Li + ) is an example of a method for synthesizing the first compound used when introducing a polymer of . As shown in the following formula (5), when introducing an acidic functional group, an acid imidazolium salt (e.g., imidazolium phosphate, etc.) can be used. Then, by using an ion exchange resin to remove the imidazolium cation and neutralizing the acidic polymer with lithium hydroxide, the counter cation of the acidic functional group is exchanged for a lithium ion.

[0054]

[0055] The first compound used in the method for producing a solid electrolyte material according to the first embodiment may be composed of one type of polymer or may be composed of a plurality of types of polymers.

[0056] The second compound is used as a crosslinking agent for crosslinking the first compound. The second compound only needs to contain an electron-donating polar group and be a polymer containing at least one second functional group having a function of reacting with the first functional group of the first compound to form a chemical bond in the molecular structural unit. The structural unit constituting the crosslinked structure contained in the polymer of the first embodiment is formed by the second compound. That is, the structural unit derived from the second compound becomes a conduction path for the alkali metal ions captured by the acidic functional group, and conducts the alkali metal ions. As a result, the solid electrolyte material of the first embodiment is considered to have high ion conductivity.

[0057] In the second compound, the second functional group used for the crosslinking reaction with the first compound may include, for example, an epoxy group. Two or more second functional groups may be included in the second compound. When two or more second functional groups are included in the second compound, the second functional groups may be the same functional groups or different functional groups.

[0058] As the above-mentioned polar group in the second compound, for example, ether group and nitrile group etc. can be listed. That is, the second compound can contain at least one selected from the group consisting of ether group and nitrile group as the above-mentioned polar group. Among them, ether group is ideal because it can further improve ion conductivity. Ether group can be a polyether group. For example, the second compound can contain ether group as the above-mentioned polar group, and can also contain polyether group. The second compound can be a polyether-based crosslinking agent containing polyether group. Ether group is, for example, polyethylene oxide.

[0059] The second compound may contain an ether group as the above-mentioned polar group and an epoxy group as the second functional group. The second compound may contain, for example, polyethylene glycol diglycidyl ether. The second compound may be substantially composed of polyethylene glycol diglycidyl ether. Here, "the second compound is substantially composed of polyethylene glycol diglycidyl ether" means that the molar ratio (i.e., molar fraction) of the total amount of polyethylene glycol diglycidyl ether to the total amount of all polymers constituting the second compound is 90% or more. As an example, the molar ratio may be 95% or more. The second compound may also be composed only of polyethylene glycol diglycidyl ether.

[0060] The Mw of the second compound is not particularly limited, and is, for example, not more than 6000. The Mw of the second compound may be, for example, not less than 100, or not less than 150. The second compound may be a polymer.

[0061] The second compound used in the method for producing the solid electrolyte material according to the first embodiment may be composed of one compound or may be composed of a plurality of compounds.

[0062] In the method for manufacturing the solid electrolyte material of the first embodiment, the specific method and steps for reacting the first compound with the second compound to crosslink, as well as the temperature conditions and other conditions can be appropriately selected according to the first compound and the second compound used. As an example, when the first compound is a polymer bonded to the main chain of cellulose by a phosphite group for capturing alkali metal ions, and the second compound is polyethylene glycol diglycidyl ether, for example, a crosslinking solution containing the second compound and a solvent is prepared, and the first compound (for example, a film formed by the first compound) is added to the crosslinking solution, and it is maintained at a temperature at which the dehydration condensation of the first compound does not occur for more than 5 hours so that the first compound reacts with the second compound, thereby obtaining the solid electrolyte material of the first embodiment. It should be noted that the temperature at which the dehydration condensation of the first compound does not occur is preferably below 150°C, for example, it can be about room temperature (25°C).

[0063] (Second embodiment)

[0064] The second embodiment will be described below. Matters already described in the first embodiment may be omitted as appropriate.

[0065] The nonaqueous electrolyte secondary battery of the second embodiment comprises: a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator disposed between the positive electrode and the negative electrode, and a nonaqueous electrolyte. The nonaqueous electrolyte secondary battery of the second embodiment satisfies at least one selected from the group consisting of the following (A) to (D):

[0066] (A) It further comprises a membrane comprising the solid electrolyte material of the first embodiment, the membrane being provided on the surface of at least one electrode selected from the group consisting of a positive electrode and a negative electrode, which faces the separator. (B) It further comprises a membrane comprising the solid electrolyte material of the first embodiment, the membrane being provided on the surface of particles of at least one active material selected from the group consisting of a positive electrode active material and a negative electrode active material. (C) It further comprises a membrane comprising the solid electrolyte material of the first embodiment, the membrane being provided on at least a portion of the surface of the separator.

[0067] (D) The separator includes the solid electrolyte material of the first embodiment.

[0068] The nonaqueous electrolyte secondary battery of the second embodiment includes the solid electrolyte material of the first embodiment in at least one of the modes described in (A) to (D) above. As described in the first embodiment, the solid electrolyte material of the first embodiment has both ion conductivity and separability of the nonaqueous solvent. Therefore, when the nonaqueous electrolyte secondary battery of the second embodiment satisfies the above (A) or (B), the nonaqueous electrolyte secondary battery of the second embodiment can suppress various problems such as side reactions generated by contact between the electrode or electrode active material and the nonaqueous solvent and the dissolution of the active material components into the nonaqueous solvent while maintaining ion conduction. In addition, when the nonaqueous electrolyte secondary battery of the second embodiment satisfies the above (C) or (D), the separator of the nonaqueous electrolyte secondary battery of the second embodiment can suppress the movement of the nonaqueous solvent while maintaining ion conduction. Therefore, it is possible to suppress the movement of byproducts generated by side reactions on one electrode side or active material components dissolved from the active material to the other electrode side. In addition, when the non-aqueous electrolyte secondary battery of the second embodiment satisfies the above-mentioned (C) or (D), for example, a non-aqueous solvent that is suitable as a non-aqueous solvent on the positive electrode side (or negative electrode side) but not suitable as a non-aqueous solvent on the negative electrode side (or positive electrode side) can be selectively used on the positive electrode side (or negative electrode side), thereby increasing the freedom of design for improving battery performance.

[0069] Figure 1 2 is a cross-sectional view schematically showing a part of the configuration of the nonaqueous electrolyte secondary battery according to the second embodiment. Here, a lithium ion secondary battery will be described as an example of the nonaqueous electrolyte secondary battery according to the second embodiment.

[0070] Figure 1 The nonaqueous electrolyte secondary battery 100 shown includes a positive electrode 1 , a negative electrode 2 , a separator 3 disposed between the positive electrode 1 and the negative electrode 2 , and a nonaqueous electrolyte. Figure 1 In the figure, reference numeral 4 represents a non-aqueous electrolyte on the positive electrode side, and reference numeral 5 represents a non-aqueous electrolyte on the negative electrode side. The positive electrode 1 includes, for example, a positive electrode collector 11 and a positive electrode active material layer 12 disposed on the positive electrode collector 11. The positive electrode active material layer 12 contains a positive electrode active material 13. The negative electrode 2 includes, for example, a negative electrode collector 21 and a negative electrode active material layer 22 disposed on the negative electrode collector 21. The negative electrode active material layer 22 contains a negative electrode active material 23.

[0071] Figure 2 Show Figure 1 The non-aqueous electrolyte secondary battery shown is a cross-sectional view of an electrode when the structure satisfies (A). Here, an example is shown when the positive electrode 1 satisfies the above (A). Figure 2The positive electrode 1 shown further includes a coating 6 disposed on the surface facing the separator 3. The coating 6 is a film containing the solid electrolyte material of the first embodiment. The coating 6 can be composed of the solid electrolyte material of the first embodiment. The coating 6 can be disposed on a portion of the surface of the positive electrode active material layer 12 facing the separator 3, or can cover the entire surface facing the separator 3. The thickness of the coating 6 is, for example, 1 nm to 1000 nm, preferably 1 nm to 100 nm. Through the coating 6, the separation of the positive electrode active material layer 12 and the non-aqueous solvent of the non-aqueous electrolyte 4 is achieved while maintaining ion conduction. Therefore, the side reaction of the positive electrode active material 13 with the non-aqueous solvent can be suppressed, and the dissolution of the active material components from the positive electrode active material 13 into the non-aqueous solvent can also be suppressed. The thickness of the coating 6 can be obtained, for example, by forming a cross section of the positive electrode 1 using a cross-section polisher (CP) and observing the cross section of the positive electrode 1 using a scanning electron microscope (SEM). It should be noted that the coating 6 can also be disposed on the negative electrode active material layer 22 of the negative electrode 2.

[0072] For example, the coating 6 can be formed by applying a dispersion of the solid electrolyte material of the first embodiment to the positive electrode active material layer 12 and drying it. The coating method is not particularly limited, and a known coating method such as slit coating and spraying can be appropriately selected. As another method, for example, a solution containing the first compound can be applied to the positive electrode active material layer 12, and then contacted with a solution containing the second compound to form the coating 6 by a cross-linking reaction of the first compound. In addition, the coating 6 can also be formed by using the solid electrolyte material of the first embodiment to form a thin film and laminating the thin film on the surface of the positive electrode active material layer 12 by transfer or the like.

[0073] Figure 3 Show Figure 1 The cross-sectional view of the active material of the non-aqueous electrolyte secondary battery shown in FIG. 1 is a cross-sectional view of the active material of the non-aqueous electrolyte secondary battery satisfying the structure (B). Here, an example is shown in which the positive electrode active material 13 satisfies the above (B). Figure 3The surface of the particles of the positive electrode active material 13 shown is provided with a coating 7 containing the solid electrolyte material of the first embodiment. The coating 7 can be composed of the solid electrolyte material of the first embodiment. The coating 7 can be provided on a part of the surface of the particles of the positive electrode active material 13, or it can cover the entire surface of the particles. The coating 7 is expected to be formed with a uniform thickness in the entire area of ​​the particle surface. The thickness of the coating 7 is, for example, 1nm to 1000nm, and is preferably 1nm to 100nm. If the thickness of the coating 7 is within this range, the coating 7 can more effectively separate the active material from the non-aqueous solvent while ensuring the smooth movement of alkali metal ions such as lithium ions. Therefore, the side reaction of the positive electrode active material 13 with the non-aqueous solvent is suppressed, and the dissolution of the active material components from the positive electrode active material 13 into the non-aqueous solvent can also be suppressed. The thickness of the coating 7 can be obtained, for example, by forming a particle cross section of the positive electrode active material 13 using CP and observing the particle cross section using SEM. It should be noted that the coating 7 may be provided on the surface of the particles of the negative electrode active material 23 of the negative electrode 2 .

[0074] The coating 7 can be formed on the surface of the particles of the positive electrode active material 13 by spray drying a raw material liquid in which the particles of the positive electrode active material 13 are dispersed and the solid electrolyte material of the first embodiment is dissolved, for example. It should be noted that as a method other than spray drying, a method of spraying a solution of a solid electrolyte material onto the particles of the positive electrode active material 13, a method of immersing the particles of the positive electrode active material 13 in a solution of a solid electrolyte material, etc. can be cited.

[0075] Figure 4 Show Figure 1 The non-aqueous electrolyte secondary battery shown in FIG. 1 is a cross-sectional view of the separator 3 when the structure (C) is satisfied. Figure 4 A separation membrane 8 including the solid electrolyte material of the first embodiment is provided on at least a portion of the surface of the separator 3 shown. Figure 4As shown, the separation membrane 8 can be arranged on one main surface of the surface of the separator 3, or on both main surfaces of the surface of the separator 3. The thickness of the separation membrane 8 is, for example, 1nm to 1000nm, and is preferably 1nm to 100nm. Through the separation membrane 6, the movement of the non-aqueous solvent is suppressed while the ion conduction of the separator 3 is maintained. That is, the movement between the non-aqueous solvent of the non-aqueous electrolyte 4 on the positive electrode side and the non-aqueous solvent of the non-aqueous electrolyte 5 on the negative electrode side is suppressed, so that the by-products produced by the side reaction on one electrode side or the active material components dissolved from the active material can be suppressed from moving to the other electrode side. In addition, a solvent suitable for the non-aqueous solvent on the positive electrode side and a solvent suitable for the non-aqueous solvent on the negative electrode side can be selected respectively and used on each electrode side. The thickness of the separation membrane 8 can be obtained, for example, by forming a cross section of a stack of the separator 3 and the separation membrane 8 using CP and observing the cross section of the stack using SEM.

[0076] The separation membrane 8 can be formed, for example, by applying a dispersion of the solid electrolyte material of the first embodiment on the surface of the separator 3 and drying it. The coating method is not particularly limited, and a known coating method such as slit coating and spraying can be appropriately selected. As another method, for example, a solution containing the first compound can be first applied to the separator 3, and then contacted with a solution containing the second compound to cause the first compound to undergo a cross-linking reaction, thereby forming the separation membrane 8. In addition, the separation membrane 8 can also be formed by using the solid electrolyte material of the first embodiment to form a thin film and laminating the thin film on the surface of the separator 3 by transfer or the like.

[0077] When the nonaqueous electrolyte secondary battery 100 satisfies the configuration (D), Figure 1 The separator 3 shown contains the solid electrolyte material of the first embodiment. The separator 3 can be composed of the solid electrolyte material of the first embodiment. When the nonaqueous electrolyte secondary battery 100 satisfies the above (D), the same effects as those when the above (C) is satisfied can be obtained.

[0078] As described above, the positive electrode 1 includes, for example, the positive electrode current collector 11 and the positive electrode active material layer 12 disposed on the positive electrode current collector 11 .

[0079] As the positive electrode current collector 11, a sheet or film made of a metal material that is stable within the potential range of the positive electrode 1, such as aluminum, stainless steel, titanium, or their alloys, can be used. Aluminum and its alloys are cheap and easy to make into thin films, so they are suitable as materials for the positive electrode current collector 11. The sheet or film can be porous or non-porous. As the sheet or film, a metal foil, a metal mesh, etc. can be used. Carbon materials such as carbon can be applied to the surface of the positive electrode current collector 11 as a conductive auxiliary material.

[0080] The positive electrode active material 13 contained in the positive electrode active material layer 12 is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions. As the positive electrode active material 13, for example, lithium-containing transition metal oxides, lithium-containing transition metal phosphates, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, transition metal oxynitrides, etc. can be used. Typically, as the positive electrode active material 13, lithium-containing transition metal oxides are used. Lithium-containing transition metal oxides are composite oxides containing transition metal elements such as Co, Mn, Ni, and Al in addition to Li. The metal elements contained in the lithium-containing transition metal oxide are, for example, at least one selected from Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among them, it is preferred to contain at least one selected from Co, Mn, Ni, and Al. Examples of lithium-containing transition metal oxides include lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, and lithium iron phosphate. The positive electrode active material 13 includes, for example, at least one selected from the group consisting of lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, and lithium iron phosphate.

[0081] The lithium-containing transition metal oxide has, for example, a layered crystal structure, and specific examples thereof include a layered structure belonging to the space group R-3m or a layered structure belonging to the space group C2 / m.

[0082] The particles of lithium-containing transition metal oxides can be secondary particles formed by the aggregation of a large number of primary particles. The volume-based median particle size (D50) of the particles of lithium-containing transition metal oxides is, for example, 3 μm to 30 μm, and is preferably 5 μm to 25 μm. In the case where the lithium-containing transition metal oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particles. D50 refers to the particle size at which the cumulative frequency in the volume-based particle size distribution becomes 50% from the smaller particle size, also known as the median diameter. The particle size distribution of the composite oxide can be measured using a laser diffraction particle size distribution measuring device (for example, MicrotracBEL Corp., MT3000II) with water as the dispersion medium.

[0083] The positive electrode active material layer 12 may include other materials such as a conductive aid and a binder. As a conductive aid, carbon black such as acetylene black and ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials may be exemplified. As a binder, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin and the like may be exemplified. In addition, these resins may also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO) and the like.

[0084] As described above, the negative electrode 2 includes, for example, the negative electrode current collector 21 and the negative electrode active material layer 22 disposed on the negative electrode current collector 21 .

[0085] As the negative electrode current collector 21, a sheet or film made of a metal material such as stainless steel, nickel, copper, or an alloy thereof that is stable within the potential range of the negative electrode 2 can be used. The sheet or film can be porous or non-porous. As the sheet or film, a metal foil, a metal mesh, etc. can be used. A carbon material such as carbon can be applied to the surface of the negative electrode current collector 21 as a conductive auxiliary material.

[0086] The negative electrode active material 23 contained in the negative electrode active material layer 22 is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions. Examples of the negative electrode active material 23 include carbon materials, silicon, silicon compounds, tin, tin compounds, lithium titanate, NiBi alloys, and the like. The negative electrode active material 23, for example, includes at least one selected from the group consisting of carbon materials, silicon, silicon compounds, tin, tin compounds, lithium titanate, and NiBi alloys. A suitable example of a carbon material is graphite such as natural graphite such as flaky graphite, blocky graphite, and earthy graphite, and artificial graphite such as blocky artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). As a negative electrode active material, graphite and silicon-containing materials such as silicon and silicon compounds may also be used in combination.

[0087] The negative electrode active material layer 22 may include other materials such as a conductive aid and a binder. As a conductive aid, the negative electrode active material layer 22 may use the same material as that which can be used in the positive electrode active material layer 13. As a binder, as in the case of the positive electrode active material layer 13, fluororesins, PAN, polyimides, acrylic resins, polyolefins, etc. may also be used, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode active material layer 22 may also include CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use SBR in combination with CMC or a salt thereof, PAA or a salt thereof.

[0088] The separator 3 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, non-woven fabrics, etc. can be listed. As the material of the separator 3, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 3 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aromatic polyamide resin can be formed on the surface of the separator 3. A filler layer containing an inorganic filler can also be formed at the interface between the separator 3 and at least one of the positive electrode 1 and the negative electrode 2. It should be noted that when the non-aqueous electrolyte secondary battery 100 of the second embodiment satisfies the above (D), the separator 3 contains the solid electrolyte material of the first embodiment.

[0089] The non-aqueous electrolyte 4 of the positive electrode side and the non-aqueous electrolyte 5 of the negative electrode side respectively include a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent can use, for example, esters, ethers, nitriles, amides, and mixed solvents of more than two of these. The non-aqueous solvent can contain a halide in which at least a portion of the hydrogen in these solvents is replaced by a halogen atom such as fluorine. As an example of a non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), 3,3,3-trifluoromethyl propionate (FMP) and their mixed solvents can be listed. Electrolyte salts may be, for example, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(perfluoroethanesulfonyl)imide (LiN(SO2C2F5)2), LiAsF6, LiCF3SO3, lithium difluoro(oxalate)borate (LiFOB), etc. One selected from these electrolyte salts may be used, or two or more may be used in combination.

[0090] Next, as a more specific configuration example of the nonaqueous electrolyte secondary battery according to the second embodiment, a nonaqueous electrolyte secondary battery having a configuration including a wound electrode body will be described. Figure 5 1 is a cross-sectional view schematically showing an axial cross section of a nonaqueous electrolyte secondary battery 200 including a wound electrode body, which is an example of the nonaqueous electrolyte secondary battery according to the second embodiment.

[0091] like Figure 5 As shown, the nonaqueous electrolyte secondary battery 200 includes a wound electrode body 34, a nonaqueous electrolyte, and an outer can 36 for storing the electrode body 34 and the nonaqueous electrolyte. The electrode body 34 includes a positive electrode 31, a negative electrode 32, and a separator 33, and has a winding structure in which the positive electrode 31 and the negative electrode 32 are wound in a spiral shape with the separator 33 interposed therebetween. The outer can 36 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 36 is sealed by a sealing body 37. In the following, for convenience of description, the sealing body 37 side of the battery 200 is referred to as the upper side, and the bottom side of the outer can 36 is referred to as the lower side.

[0092] The nonaqueous electrolyte secondary battery 200 , like the above-described nonaqueous electrolyte secondary battery 100 , includes the solid electrolyte material of the first embodiment in at least one of the aspects described in (A) to (D).

[0093] The positive electrode 31, the negative electrode 32 and the separator 33 constituting the electrode body 34 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 34 by being wound into a spiral shape. The negative electrode 32 is formed to be one circle larger than the positive electrode 31 to prevent the precipitation of lithium. That is, the negative electrode 32 is formed longer than the positive electrode 31 in the length direction and the width direction (that is, the lateral direction). The separator 33 is formed to be at least one circle larger than the positive electrode 31, for example, two sheets are arranged in a manner of clamping the positive electrode 31. The electrode body 34 has a positive electrode lead 40 connected to the positive electrode 31 by welding or the like, and a negative electrode lead 41 connected to the negative electrode 32 by welding or the like.

[0094] It should be noted that, here, as a more specific configuration example of the nonaqueous electrolyte secondary battery of the second embodiment, a cylindrical battery in which the electrode body 34 having a winding structure is accommodated in the outer packaging can 36 of a bottomed cylindrical shape is exemplified, but the electrode body may also be a laminated electrode body in which a plurality of positive electrodes and negative electrodes are alternately laminated one by one through a separator. In addition, the form of the nonaqueous electrolyte secondary battery of the second embodiment is not limited to a cylindrical shape, and may be a square battery, a laminated battery, a coin-shaped battery, etc.

[0095] The positive electrode 31 includes a positive electrode collector 31a and a positive electrode active material layer 31b formed on the positive electrode collector 31a. The positive electrode active material layer 31b is preferably formed on both sides of the positive electrode collector except for the exposed portion where the positive electrode lead 40 is welded. The positive electrode 31 can be manufactured, for example, by coating a positive electrode slurry containing a positive electrode active material, a conductive additive, and a binder on the positive electrode collector 31a, drying the coating film, and then compressing it to form the positive electrode active material layer 31b on both sides of the positive electrode collector 31a. It should be noted that the detailed descriptions of the positive electrode collector 31a, the positive electrode active material layer 31b, and the positive electrode active material, conductive aid and binder contained in the positive electrode active material layer 31b in the positive electrode 31 are respectively the same as the positive electrode collector 11, the positive electrode active material layer 12, and the positive electrode active material 13, conductive aid and binder contained in the positive electrode 1 of the non-aqueous electrolyte secondary battery 100.

[0096] The negative electrode 32 includes a negative electrode collector 32a and a negative electrode active material layer 32b formed on the negative electrode collector 32a. The negative electrode active material layer 32b is preferably formed on both sides of the negative electrode collector 32a except for the exposed portion where the negative electrode lead 31 is welded. The negative electrode 32 can be manufactured by applying a negative electrode slurry containing a negative electrode active material, a conductive additive, a binder, etc. on the surface of the negative electrode collector 32a, drying the coating film, and then compressing it to form the negative electrode active material layer 32b on both sides of the negative electrode collector. It should be noted that the detailed descriptions of the negative electrode collector 32a, the negative electrode active material layer 32b, and the negative electrode active material, conductive aid and binder contained in the negative electrode active material layer 32b in the negative electrode 32 are respectively the same as the negative electrode collector 21, the negative electrode active material layer 22, and the negative electrode active material 23, conductive aid and binder contained in the negative electrode 2 of the non-aqueous electrolyte secondary battery 100.

[0097] The detailed description of the separator 33 is the same as that of the separator 3 in the nonaqueous electrolyte secondary battery 100 .

[0098] Insulating plates 38 and 39 are disposed above and below the electrode body 34 , respectively. Figure 5 In the example shown, the positive electrode lead 40 extends to the sealing body 37 side through the through hole of the insulating plate 38, and the negative electrode lead 41 extends to the bottom side of the outer can 36 through the outer side of the insulating plate 39. The positive electrode lead 40 is connected to the lower surface of the internal terminal plate 43 of the sealing body 37 by welding or the like, and the top plate of the sealing body 37, that is, the cover 47 electrically connected to the internal terminal plate 43, serves as the positive terminal. The negative electrode lead 41 is connected to the bottom inner surface of the outer can 36 by welding or the like, and the outer can 36 serves as the negative terminal.

[0099] A gasket 48 is provided between the outer can 36 and the sealing body 37 to ensure the airtightness inside the battery. A groove portion 32 is formed on the outer can 36, with a portion of the side portion bulging inwardly, to support the sealing body 37. The groove portion 42 is preferably formed in an annular shape along the circumferential direction of the outer can 36, and the sealing body 37 is supported by its upper surface. The sealing body 37 is fixed to the upper part of the outer can 36 through the groove portion 32 and the open end of the outer can 36 fastened to the sealing body 37.

[0100] The sealing body 37 has a structure in which an internal terminal plate 43, a lower valve body 44, an insulating member 45, an upper valve body 46 and a cover 47 are stacked in order from the electrode body 34 side. The components constituting the sealing body 47 have, for example, a disc shape or a ring shape, and the components except the insulating member 45 are electrically connected to each other. The lower valve body 44 and the upper valve body 46 are connected at their respective central portions, and an insulating member 45 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 44 is deformed and broken in a manner that pushes the upper valve body 46 toward the cover 47 side, thereby cutting off the current path between the lower valve body 44 and the upper valve body 46. When the internal pressure rises further, the upper valve body 46 breaks, and the gas is discharged from the opening of the cover 47.

[0101] (Other Embodiments)

[0102] (appendix)

[0103] Based on the description of the above embodiments, the following technology is disclosed.

[0104] (Technology 1)

[0105] A solid electrolyte material, which is a solid electrolyte material for a non-aqueous electrolyte secondary battery,

[0106] The solid electrolyte material comprises a polymer having an acidic functional group having an alkali metal ion bonded to the main chain.

[0107] The polymer has a cross-linked structure including an electron-donating polar group.

[0108] With this configuration, it is possible to provide a solid electrolyte material for a non-aqueous electrolyte secondary battery that can achieve both ion conductivity and non-aqueous solvent separability (solvent separability).

[0109] (Technique 2)

[0110] The solid electrolyte material according to technology 1, wherein the acidic functional group is a phosphite group.

[0111] With this configuration, the ion conductivity of the solid electrolyte material can be improved.

[0112] (Technique 3)

[0113] The solid electrolyte material according to technology 1 or 2, wherein the main chain of the polymer contains at least one selected from the group consisting of cellulose, cellulose derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polyethylene oxide, polyethylene oxide derivatives, polyethylene glycol, and polyethylene glycol derivatives.

[0114] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0115] (Technique 4)

[0116] The solid electrolyte material according to any one of techniques 1 to 3, wherein the cross-linked structure includes at least one selected from the group consisting of an ether group and a nitrile group as the polar group.

[0117] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0118] (Technique 5)

[0119] The solid electrolyte material according to Technology 4, wherein the ether group is a polyethylene oxide group.

[0120] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0121] (Technique 6)

[0122] The solid electrolyte material according to any one of techniques 1 to 5, wherein the cross-linked structure includes a structure represented by the following formula (1).

[0123]

[0124] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0125] (Technique 7)

[0126] The solid electrolyte material according to Technology 6, wherein the cross-linked structure includes a structure represented by the following formula (2).

[0127]

[0128] In the above formula (2), n represents a positive integer.

[0129] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0130] (Technology 8)

[0131] A non-aqueous electrolyte secondary battery comprising:

[0132] A positive electrode including a positive electrode active material,

[0133] A negative electrode including a negative electrode active material,

[0134] a separator disposed between the positive electrode and the negative electrode, and

[0135] Non-aqueous electrolytes,

[0136] The nonaqueous electrolyte secondary battery satisfies at least one selected from the group consisting of the following (A) to (D):

[0137] (A) The nonaqueous electrolyte secondary battery further comprises a film containing the solid electrolyte material according to any one of techniques 1 to 7, the film being provided on a surface of at least one electrode selected from the group consisting of the positive electrode and the negative electrode that faces the separator.

[0138] (B) The nonaqueous electrolyte secondary battery further comprises a film containing the solid electrolyte material according to any one of techniques 1 to 7, the film being provided on the surface of particles of at least one active material selected from the group consisting of the positive electrode active material and the negative electrode active material.

[0139] (C) The nonaqueous electrolyte secondary battery further comprises a film containing the solid electrolyte material according to any one of techniques 1 to 7, wherein the film is provided on at least a portion of the surface of the separator.

[0140] (D) The aforementioned separator contains the solid electrolyte material described in any one of Techniques 1 to 7.

[0141] According to this configuration, the solid electrolyte material having both ion conductivity and solvent separation properties can be used for separation between the components of the nonaqueous electrolyte secondary battery. Therefore, according to this configuration, the performance and reliability of the nonaqueous electrolyte secondary battery can be improved.

[0142] (Technique 9)

[0143] According to the non-aqueous electrolyte secondary battery described in Technology 8, the aforementioned positive electrode active material includes at least one selected from the group consisting of lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium iron phosphate, and the aforementioned negative electrode active material includes at least one selected from the group consisting of carbon material, silicon, silicon compound, tin, tin compound, lithium titanate and NiBi alloy.

[0144] According to this configuration, a high-performance and highly reliable lithium-ion secondary battery can be obtained.

[0145] (Technology 10)

[0146] A method for producing a solid electrolyte material, which is a method for producing a solid electrolyte material for a non-aqueous electrolyte secondary battery.

[0147] The production method comprises a step of reacting a first compound with a second compound having an electron-donating polar group to perform cross-linking, wherein the first compound is a polymer having an acidic functional group of an alkali metal ion bonded to the main chain,

[0148] The first compound comprises a first functional group,

[0149] The second compound includes at least one second functional group in the molecular structural unit, and the second functional group has a function of reacting with the first functional group to form a chemical bond.

[0150] With this configuration, it is possible to provide a solid electrolyte material for a non-aqueous electrolyte secondary battery that can achieve both ion conductivity and solvent separability.

[0151] (Technology 11)

[0152] The production method according to technology 10, wherein the main chain of the first compound includes at least one selected from the group consisting of cellulose, cellulose derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polyethylene oxide, polyethylene oxide derivatives, polyethylene glycol, and polyethylene glycol derivatives.

[0153] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0154] (Technology 12)

[0155] The solid electrolyte material according to technology 10 or 11, wherein the second functional group of the second compound includes an epoxy group.

[0156] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0157] (Technology 13)

[0158] The production method according to any one of Techniques 10 to 12, wherein the second compound contains at least one selected from the group consisting of an ether group and a nitrile group as the polar group.

[0159] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0160] (Technology 14)

[0161] The production method according to Technology 13, wherein the ether group is a polyethylene oxide group.

[0162] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0163] (Technology 15)

[0164] The production method according to any one of Techniques 10 to 14, wherein the second compound comprises polyethylene glycol diglycidyl ether.

[0165] With this configuration, the ion conductivity and solvent separation properties of the solid electrolyte material can be improved.

[0166] Example

[0167] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.

[0168] <Example 1>

[0169] [Synthesis of solid electrolyte materials]

[0170] (Synthesis of the first compound)

[0171] First, the first compound is synthesized. The synthesis steps of the first compound are as follows.

[0172] (1) 0.5 g of cellulose (Mw: about 300,000) was dispersed in 2 mL of dimethyl sulfoxide (DMSO).

[0173] (2) 24.5 g of 1-ethyl-3-methylimidazolium methylphosphonate was weighed and placed in an eggplant-shaped flask. A stirring bar was added and the mixture was heated at 80°C.

[0174] (3) The cellulose dispersion obtained in (1) was placed in the above-mentioned eggplant-shaped flask, and the contents were stirred at 80° C. to dissolve the cellulose.

[0175] (4) Heat the contents to 100°C and stir for 48 hours.

[0176] (5) The reaction solution was diluted with water and purified with ultrapure water using a dialysis membrane.

[0177] (6) The obtained aqueous solution is mixed with a strongly acidic ion exchange resin to remove the imidazolium cation at the terminal of the phosphite group.

[0178] (7) A lithium hydroxide aqueous solution is added to the acidic aqueous solution to neutralize it and lithiate the terminal phosphite groups.

[0179] (8) The obtained aqueous solution was concentrated using a rotary evaporator, and the concentrate was placed in a PFA plate petri dish for natural drying.

[0180] (9) The film obtained on the culture dish is vacuum dried at 100° C. to obtain phosphorylated cellulose containing lithium ions.

[0181] As described above, the synthesis method of the lithium ion-containing phosphitylated cellulose as the first compound is represented by the following formula (5).

[0182]

[0183] (Cross-linking method of the first compound)

[0184] Next, the obtained first compound is reacted with a second compound as a crosslinking agent to crosslink the first compound using the second compound. The steps of the crosslinking method are as follows.

[0185] (1) A 1 mass % aqueous solution of the lithium ion-containing phosphitylated cellulose obtained by the above-mentioned synthesis method is prepared. The aqueous solution of the lithium ion-containing phosphitylated cellulose is cast into a petri dish and dried to produce a membrane of the lithium ion-containing phosphitylated cellulose.

[0186] (2) The obtained lithium ion-containing phosphitylated cellulose membrane was placed in a crosslinking solution containing polyethylene glycol diglycidyl ether (polymerization degree n=9) as the second compound, and maintained at 60°C for 3 hours to react the lithium ion-containing phosphitylated cellulose membrane with polyethylene glycol diglycidyl ether. As the crosslinking solution, a 2-propanol solution containing polyethylene glycol diglycidyl ether at a concentration of 0.5 mol / L and LiOH at a concentration of 0.0017 mol / L was used.

[0187] (3) The membrane obtained in (2) was washed with 70% by mass of methanol and dried to obtain a membrane of a solid electrolyte material having a cross-linked structure.

[0188] The thickness of the film of the solid electrolyte material having a cross-linked structure obtained in Example 1 was 18 μm.

[0189] [Evaluation of Solvent Separability]

[0190] A test for evaluating the solvent separation performance (hereinafter referred to as the solvent separation test) was conducted using an H-type battery for the membrane of the solid electrolyte material having a cross-linked structure obtained by the above method. A non-aqueous electrolyte for the positive electrode (positive electrode solution) was placed in one battery cell of the H-type battery, and a non-aqueous electrolyte for the negative electrode (negative electrode solution) was placed in the other battery cell, and the two battery cells were separated by the membrane of the solid electrolyte material having a cross-linked structure of Example 1. The positive electrode solution and the negative electrode solution are as follows.

[0191] Cathode solution: 0.7M LiPF6 / FEC+FMP (FEC / FMP=2 / 8 (volume ratio))

[0192] Anode solution: 3M LiTFSI+0.1M LiFOB / DME

[0193] After the test battery cell was kept at 25°C for 50 hours, the amount of the solvent (DME) of the negative electrode solution mixed into the battery to which the positive electrode solution was added was quantitatively analyzed using H-NMR. The migration coefficient of the solvent (DME) to the positive electrode side was calculated based on the amount of DME mixed, the film thickness and area of ​​the solid electrolyte material membrane, and the concentration difference. The results are shown in Table 1 below. It should be noted that "concentration difference" refers to the difference in the initial bulk concentration of the target non-aqueous solvent between the positive electrode solution and the negative electrode solution. In this embodiment, it refers to the molar concentration of DME in the negative electrode solution before the solvent separation test. Here, the unit of the migration coefficient is "mol·cm / (h·cm 2 ·mol / L)", and the units constituting the units in the migration coefficient are shown below.

[0194] mol: DME concentration detected on the cathode side

[0195] cm: Film thickness of solid electrolyte material film

[0196] h: time of solvent separation test (50 hours in this example)

[0197] cm 2 : The area of ​​the solid electrolyte material membrane

[0198] mol / L: concentration difference (in this example, the DME concentration in the cathode solution before the solvent separation test)

[0199] In addition, the liquid separation rate after 10 years was calculated. Specifically, the solvent separation test was evaluated at two different time points, and a plot was made according to the square root law (horizontal axis = √(time), vertical axis = liquid separation rate), and the value after 10 years was calculated by extrapolation. The liquid separation rate is the value obtained by subtracting the molar ratio of DME in the cathode solution from 100 when the molar ratio is set to FEC+FMP+DME=100.

[0200] [Evaluation of ion conductivity]

[0201] The membrane of the solid electrolyte material having a cross-linked structure of Example 1 was used to measure the ionic conductivity and Li + The migration number was measured.

[0202] A non-blocking electrode in which a film of the solid electrolyte material having a cross-linked structure of Example 1 is sandwiched between metal lithium electrodes was arranged in a measurement cell, and the impedance of the solid electrolyte material was measured by AC impedance measurement at 60°C.

[0203] In the Nyquist diagram obtained by impedance measurement, the actual impedance value measured at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the membrane of the solid electrolyte material to ion conduction. Based on the following formula (6), the ion conductivity is calculated using this resistance value.

[0204] σ +、- =(R SE ×S / t) -1 ……(6)

[0205] In formula (6), σ +、- represents the ion conductivity in the AC impedance measurement. S represents the area of ​​the solid electrolyte material membrane. R SE represents the resistance value of the solid electrolyte material film in the AC impedance measurement. t represents the thickness of the solid electrolyte material film.

[0206] In addition, the above-mentioned non-blocking electrode was arranged in the measurement cell, and the DC resistance σ was also measured in the constant voltage measurement. + .

[0207] By calculating the DC resistance σ in constant voltage measurement + Relative to the ionic conductivity σ in the AC impedance measurement +、- The ratio (σ + / σ +、- ), and thus find Li + Number of migrations.

[0208] The ionic conductivity σ in the AC impedance measurement +、- , Ionic conductivity σ in constant voltage measurement + Li + The results of migration numbers are shown in Table 2.

[0209] <Example 2>

[0210] [Synthesis of solid electrolyte materials]

[0211] In the crosslinking method of the first compound, a solid electrolyte material was synthesized in the same manner as in Example 1 except that the crosslinking reaction time was changed from 3 hours to 20 hours. The film thickness of the solid electrolyte material having a crosslinked structure obtained in Example 2 was 11 μm.

[0212] [Evaluation of Solvent Separability]

[0213] The solvent separation property of the film of the solid electrolyte material of Example 2 was evaluated by the same method as in Example 1. The results are shown in Table 1.

[0214] [Evaluation of ion conductivity]

[0215] The ion conductivity of the film of the solid electrolyte material of Example 2 was evaluated by the same method as in Example 1. Table 2 shows the results.

[0216] <Reference Example 1>

[0217] Using the film of the first compound prepared in Example 1, the solvent separability and ion conductivity were evaluated by the same method as in Example 1. The thickness of the film of the first compound obtained in Reference Example 1 was 35 μm. The results of the solvent separability are shown in Table 1. It should be noted that, with respect to the ion conductivity, no arc could be confirmed in the Nyquist plot obtained by the AC impedance measurement, and the ion conductivity was not confirmed.

[0218] [Table 1]

[0219]

[0220] [Table 2]

[0221]

[0222] As can be seen from Tables 1 and 2, the membranes of the solid electrolyte materials of Examples 1 and 2 composed of polymers having a cross-linked structure have ion conductivity and high solvent separation properties. In contrast, the membrane of Reference Example 1 composed of polymers not having a cross-linked structure has lower solvent separation properties than the membranes of Examples 1 and 2, and further, ion conductivity cannot be confirmed. These results confirm that the solid electrolyte material disclosed in the present invention has both ion conductivity and non-aqueous solvent separation properties.

[0223] Industrial Applicability

[0224] The technology of the present disclosure is useful in lithium secondary batteries.

Claims

1. A solid electrolyte material, which is a solid electrolyte material for a non-aqueous electrolyte secondary battery, The solid electrolyte material comprises a polymer having an acidic functional group of an alkali metal ion bonded to the main chain, The polymer has a cross-linked structure including an electron-donating polar group.

2. The solid electrolyte material according to claim 1, wherein The acidic functional group is a phosphite group. 3 . The solid electrolyte material according to claim 1 , wherein the main chain of the polymer comprises at least one selected from the group consisting of cellulose, cellulose derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polyethylene oxide, polyethylene oxide derivatives, polyethylene glycol, and polyethylene glycol derivatives.

4. The solid electrolyte material according to claim 1, wherein The cross-linked structure includes at least one selected from the group consisting of an ether group and a nitrile group as the polar group.

5. The solid electrolyte material according to claim 4, wherein The ether group is a polyethylene oxide group.

6. The solid electrolyte material according to claim 1, wherein The cross-linked structure comprises a structure represented by the following formula (1):

7. The solid electrolyte material according to claim 6, wherein The cross-linked structure comprises a structure represented by the following formula (2): In the formula (2), n represents a positive integer.

8. A non-aqueous electrolyte secondary battery comprising: A positive electrode including a positive electrode active material, A negative electrode including a negative electrode active material, a separator disposed between the positive electrode and the negative electrode, and Non-aqueous electrolytes, The nonaqueous electrolyte secondary battery satisfies at least one selected from the group consisting of the following (A) to (D): (A) the nonaqueous electrolyte secondary battery further comprises a membrane comprising the solid electrolyte material according to claim 1, the membrane being provided on a surface of at least one electrode selected from the group consisting of the positive electrode and the negative electrode facing the separator; (B) the nonaqueous electrolyte secondary battery further comprises a film comprising the solid electrolyte material according to claim 1, the film being provided on the surface of particles of at least one active material selected from the group consisting of the positive electrode active material and the negative electrode active material; (C) the nonaqueous electrolyte secondary battery further comprises a film comprising the solid electrolyte material according to claim 1, the film being provided on at least a portion of the surface of the separator; (D) The separator comprises the solid electrolyte material according to claim 1.

9. The nonaqueous electrolyte secondary battery according to claim 8, wherein The positive electrode active material includes at least one selected from the group consisting of lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium iron phosphate, The negative electrode active material includes at least one selected from the group consisting of carbon materials, silicon, silicon compounds, tin, tin compounds, lithium titanate, and NiBi alloys.

10. A method for producing a solid electrolyte material, which is a method for producing a solid electrolyte material for a non-aqueous electrolyte secondary battery. The production method comprises a step of reacting a first compound with a second compound having an electron-donating polar group to perform cross-linking, wherein the first compound is a polymer having an acidic functional group of an alkali metal ion bonded to the main chain, The first compound comprises a first functional group, The second compound includes at least one second functional group in a molecular structural unit, and the second functional group has a function of reacting with the first functional group to form a chemical bond.

11. The manufacturing method according to claim 10, wherein: The main chain of the first compound includes at least one selected from the group consisting of cellulose, cellulose derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polyethylene oxide, polyethylene oxide derivatives, polyethylene glycol, and polyethylene glycol derivatives.

12. The manufacturing method according to claim 10, wherein: The second functional group of the second compound includes an epoxy group.

13. The manufacturing method according to claim 10, wherein: The second compound includes at least one selected from the group consisting of an ether group and a nitrile group as the polar group.

14. The manufacturing method according to claim 13, wherein: The ether group is a polyethylene oxide group.

15. The manufacturing method according to claim 10, wherein: The second compound includes polyethylene glycol diglycidyl ether.

Citation Information

Patent Citations

  • All-solid lithium battery

    WO2007004590A1